Globalization and a high-tech economy : California, the United States and beyond - Bardhan, Ashok Deo; Jaffee, Dwight M.; Kroll, Cynthia A.; SpringerLink (online služba) (Boston, MA : Springer US, 2004)
High-technology and globalization are arguably the two most important forces driving the US economy today. This book analyzes how they interact and the implications of that interaction. The methodology applies data and statistical analysis to determine the impact of these forces over a broad spectrum of the US economy. Key topics addressed include why the US economy runs a continuing trade deficit in manufactured high-tech goods, why high-tech firms steadily lose manufacturing jobs, while creating professional jobs, and why high-tech industries rely on foreign outsourcing for much of their manufacturing.
Globalization and a High-Tech Economy -- International Trade and California Industry -- Foreign Outsourcing and Domestic Industry -- Intra-Firm Trade and Intermediate Inputs -- International Networks and High-Tech Exports -- Global Linkages, the High-Tech Sector, and State Policy Choices -- Conclusions.
Elektronická reprodukce.
Keywords: high-tech -- Kalifornie; globalizace; high-tech -- California; globalization; Spojené státy americké -- národní hospodářství; United States -- national economy; monografie; elektronické knihy; e-knihy online; monographs; electronic books; e-books online